Surgical errors of incisional gastropexy in two dogs. Issue 2 (16th May 2018) - Cray, Megan Theresa; Selmic, Laura Elizabeth; Lai, Grace Pei‐Chun; Tulipan, Rachel Jane
Abstract : Gastric dilatation volvulus (GDV) is a common life‐threatening surgical emergency seen in large and giant breed dogs. Incisional gastropexy is a common surgical procedure used to treat GDV following gastric derotation and for prevention of GDV in those breeds at risk for developing GDV. This manuscript describes two specific surgical errors that occurred during an incisional gastropexy procedure in two dogs. Both surgical errors were addressed with a second surgery and resulted in good outcomes. This report highlights specific surgical errors that can occur when performing an incisional gastropexy and discusses how to avoid these adverse events.